O1-S04.05 Incidence and prevalence of sexually transmitted infections among school students in the Eastern Cape, South Africa. (10th July 2011) - Radebe, F; Jemmott, J; Klopper, A; Jemmott, L; O'Leary, A; Ngwane, Z; Carty, C; Tyler, J; Maseko, V; Lewis, D
Abstract : Background: Although STIs are an important co-factor for HIV acquisition, few community-based STI prevalence/incidence data exist for youth in South Africa. Methods: School students (n=1057), enrolled in a cluster-randomised intervention trial in the Eastern Cape, were tested for STIs at the 42 (42M) and 54 (54M) month follow-up visits. Students filled in questionnaires, provided blood for herpes simplex type 2 (HSV-2) serology (HerpeSelect IgG, Focus Diagnostics) and urine to test for Neisseria gonorrhoeae (NG), Chlamydia trachomatis (CT) and Trichomonas vaginalis (TV) (Aptima Combo 2 and Aptima TV, GenProbe). Positive NG/CT/TV results were confirmed by other assays (Aptima NG, Aptima CT, Gen-Probe; T vaginalis Real-TM, Sacace Biotechnologies). Students with NG/CT/TV received treatment and partner follow-up; those with HSV-2 infection were counselled. STI prevalence was determined by gender at each visit; overall incidence was estimated using results for all students attending both visits and also for a subgroup who reported ever having had vaginal intercourse. Descriptive statistical analysis was performed and associations investigated with the χ 2 test. Results: 959 (91%) and 977 (92%) students tested for STIs at 42M and 54M, respectively. The students' mean age (SD) was 15.8 (1.25) years at 42M and 16.8 (1.25) years at 54M. At 42M, 149 (15.5%) had curable STIs and 67 (7.0%) had HSV-2 infection. At 54M, 154 (15.8%) had curable STIs and 104 (10.7%) had HSV-2 infection. All curable STIs were treated. Females had a higher prevalence of all pathogens at both visits (p<0.001 for all, Abstract O1-S04.05 table 1 ). Overall annual incidence rates (per 1, 000, 95% CI), based on results of the 934 (96%) students who attended the 42M/54M visits (934 urine, 931 serology tests), were substantially higher in females compared to males [males: GC 18.4 (8.7–36.6), CT 73.7 (52.4–102.5), TV 0.0 (0.0–10.6), HSV-2 28.6 (15.9–59.9); females: GC 76.0 (55.6–102.8), CT 184.0 (152.7–220.4), TV 40.0 (25.7–61.3), HSV-2 64.4 (44.9–91.3)]. Incidence rates were also calculated for students (311 females, 66%; 334 males, 77%) who reported ever having had vaginal intercourse (Abstract O1-S04.05 table 1 ). Compared to overall rates, females had significantly higher rates for each STI (GC/CT, p<0.001; TV, p =0.027; HSV-2, p =0.015); this was not the case for males. Conclusions: This community-based screening study demonstrates an extremely high STI burden among youth in the Eastern Cape Province of South Africa.